2020
DOI: 10.12965/jer.2040216.108
|View full text |Cite
|
Sign up to set email alerts
|

Swimming exercise ameliorates mood disorder and memory impairment by enhancing neurogenesis, serotonin expression, and inhibiting apoptosis in social isolation rats during adolescence

Abstract: Social isolation during adolescence is associated with anxiety, depression, and memory impairment. Exercise has been reported as a positive effect on brain function, especially hippocampus. The present study examined the effect of swimming exercise on apoptosis, cell proliferation, and serotonin expression in social isolation rats during adolescence stage. Social isolation started at postnatal day 21 and continued for 6 weeks. The rats in the swimming group were forced to swim for 60 min once daily during 6 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 27 publications
(33 reference statements)
4
28
0
Order By: Relevance
“…Compared to the rats that received 2 per cage, isolated rats had a significantly reduced BDNF concentration in the hippocampus, while no change was observed in other brain regions examined such as prefrontal cortex and striatum (Scaccianoce et al, 2006). BDNF and TrkB expression in the hippocampus was suppressed in the social isolation rats (Park et al, 2020). In this study, hippocampal BDNF and TrkB expression were decreased in the rats of the social isolation group compared to the control rats.…”
Section: Discussionmentioning
confidence: 41%
See 2 more Smart Citations
“…Compared to the rats that received 2 per cage, isolated rats had a significantly reduced BDNF concentration in the hippocampus, while no change was observed in other brain regions examined such as prefrontal cortex and striatum (Scaccianoce et al, 2006). BDNF and TrkB expression in the hippocampus was suppressed in the social isolation rats (Park et al, 2020). In this study, hippocampal BDNF and TrkB expression were decreased in the rats of the social isolation group compared to the control rats.…”
Section: Discussionmentioning
confidence: 41%
“…Social isolation and chronic unpredictable mild stress showed depressive behavior and exhibited mixed apoptosis/autophagy characteristics (Wang et al, 2019). Social isolation rats during adolescence showed increased in Bax expression and decreased in Bcl-2 expression compared to the group-housed rats (Park et al, 2020). In this study, Bax expression was increased, Bcl-2 expression was decreased, and cleaved caspase-3 expression in the hippocampus was increased in the rats of the social isolation group compared to the control rats.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Regular treadmill exercise has improved isolation-induced depression-like behavior by regulating the hypothalamic-pituitary-adrenal (HPA) axis and this type of exercise has decreased stress hormones. Additionally, increased BDNF, NGF, serotonergic cells, and brain plasticity in the hippocampus have occurred after physical activity (22,106).…”
Section: Non-drug Treatmentsmentioning
confidence: 99%
“…There is a connection between SI, learning, and memory impairments as well. Some studies have reported that environmental factors play a significant role in brain development and cognitive function in rodents, which directly affect learning and memory performance (22,23). Results suggest that SI as the lack of presence of others or the few numbers of meaningful relationships is vastly associated with many aspects of memory and learning impairment (24,25).…”
Section: Introductionmentioning
confidence: 99%